Construction of Feminism and Gender Equality in Social Media - Ariani, Diah; Sunarto, Sunarto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The criticism that produced BPFA in the Beijing Conference did not necessarily pave the way for gender equality. From the report "The Global Gap Index 2020," it is known that Indonesia got a score of 0.70 and was ranked 85th out of 153 countries, and it was also said that there had been no change in value since 2018. The feminism movement on Instagram with the @indonesiabutuhfeminis account is interesting to study because this account often provides education about feminism and gender equality. The role of the media in presenting women and men according to patriarchal standards, which was then slowly straightened out by the feminist movement with the use of new media, became an exciting thing to study. The purpose of this research is to see how the @indonesiabutuhfeminis account does in expressing gender justice through uploaded content and how they respond to the gender stigma that has existed so far. On this basis, researchers are interested in exploring feminist content campaigned on this account. The researcher uses a qualitative descriptive approach with a critical paradigm to explore in-depth and detailed social phenomena. Feminist communication theory and liberal feminist are used in this study. The data in this research is screenshots of feminism and gender equality content, captions on the @indonesiabutuhfeminis account, and supporting data relevant to the research. The data analysis technique uses Sara Mills critical discourse analysis to see how the position of the actors is represented in the text. The study results found that the two main issues raised, namely the issue of feminism and gender equality, were an effort carried out by @indonesiabutuhfeminis as the subject of this research to involve the community in the formation of a society that is aware of gender equality. Through the two main issues described the construction of feminism and gender equality, they then rearrange the concept of feminism and gender equality from the perspective of women and men.